Review article on hemodialysis and its complications - Singh, Manav; Srinivas Nayak, S.P.; Tiwari, Preeti; Shaikh, Sahil; Gautam, Vaidik; Waman Ghatol, Prajwal (Asian Journal of Pharmaceutical Research and Development, 2023)
The ability to evaluate outcomes among patients with ESRD increased dramatically after 1988, when the United States Renal Data System (USRDS) was established to record and issue reports that would track mortality and morbidity and determine factors affecting clinical outcomes. Hemodialysis is now substantially safer than it was initially, and deaths directly related to the dialysis procedure are rare. Improved dialysate delivery systems, more reliable monitoring devices, and automated safety mechanisms have reduced the risk of complications. Other technical improvements include the standard use of the more physiologic bicarbonate-based dialysate, better water-quality standards, volumetric ultrafiltration controls, and computer-controlled sodium and potassium modeling. Several in-line devices now allow dynamic monitoring of the rate of blood flow through the vascular access, changes in the hematocrit, and changes in the electrical conductivity of the dialysate, but the complication related to dialysis has not decreased as a result complication related to dialysis is persistent.